Chances and risks of supranational integration - Friedhelm Hengsbach (Intereconomics, 1978)
Although a sceptical view may rightly be taken of the efforts of the developing countries for their integration with the world economy in the framework of a New International Economic Order and the Lomé Convention, these efforts indicate a willingness of the developing countries to play a part in international and supranational integration. The opportunities and hazards of an association of the African states with the European Communities are assessed in the following article from the viewpoint of a geo-economic integration policy.
Keywords: 330; Integration